A Framework of Blockchain Technology in Intelligent Water Management - Xia, Wenjun; Chen, Xiaohong; Song, Chao (Frontiers in Environmental Science, 2022)
At present, the water resources information management in China is mainly a centralized model, and there exist some problems such as high cost, low efficiency and data storage insecurity. Blockchain technology provides a good solution, which can create an efficient trust mechanism among the links in the process of water resources utilization. And it guarantees the security of the data, avoiding the sudden collapse of the central institutions caused by some normal operations of the entire system. Based on a decentralization blockchain, we propose a decentralized water resources information management system for the whole process of "supply-use-consumption-discharge", which improve the traditional water data storage. Specifically, the monitoring and business data are encrypted by blockchain and are transmitted using a peer-to-peer network. Besides, the centralized management mode is changed and part of management work is dispersed to each node. Thus, decisions and measures can be made and implemented quickly after discovering problems to improve the efficiency of information transmission and management. In addition, two typical blockchain-based application scenarios for water resource management are designed. A blockchain-based approach makes issuing and monitoring water abstraction permits more convenient and obtaining license information more secure and verifiable. A reliable mechanism for tracing water quality ensures the accuracy and reliability of water quality information, enables the detection of locations with inadequate water quality and clarifies people’s responsibility, thus guaranteeing the water safety of residents.